2021
DOI: 10.3390/catal11070760
|View full text |Cite
|
Sign up to set email alerts
|

Solventless Mechanochemical Fabrication of ZnO–MnCO3/N-Doped Graphene Nanocomposite: Efficacious and Recoverable Catalyst for Selective Aerobic Dehydrogenation of Alcohols under Alkali-Free Conditions

Abstract: Catalytic efficacy of metal-based catalysts can be significantly enhanced by doping graphene or its derivatives in the catalytic protocol. In continuation of previous work regarding the catalytic properties of highly-reduced graphene oxide (HRG), graphene-oxide (GO) doped mixed metal oxide-based nanocomposites, herein we report a simple, straightforward and solventless mechanochemical preparation of N-doped graphene (NDG)/mixed metal oxide-based nanocomposites of ZnO–MnCO3 (i.e., ZnO–MnCO3/(X%-NDG)), wherein N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…This software demonstrated a typical FT-IR spectrum of biologically-induced mineralization of MnCO 3 , as shown in Fig. 2 The spectral peaks in MCP-4 to MCP-9 centered at 1420.90 cm −1 , 865.67 cm −1 , and 717.91 cm −1 are related to C O binding and are known to be the typical peaks of rhodochrosite material or MnCO 3 [ 29 , 41 , 50 , 80 , 86 ]. The broader peak at 3452.24 cm −1 correlated to O–H binding and N–H binding, which were related to the characteristics of the hydroxyl and amino groups and could be attributed to sugars, carboxylic acids, nucleic acids, or amino acids [ 26 ].…”
Section: Resultsmentioning
confidence: 85%
“…This software demonstrated a typical FT-IR spectrum of biologically-induced mineralization of MnCO 3 , as shown in Fig. 2 The spectral peaks in MCP-4 to MCP-9 centered at 1420.90 cm −1 , 865.67 cm −1 , and 717.91 cm −1 are related to C O binding and are known to be the typical peaks of rhodochrosite material or MnCO 3 [ 29 , 41 , 50 , 80 , 86 ]. The broader peak at 3452.24 cm −1 correlated to O–H binding and N–H binding, which were related to the characteristics of the hydroxyl and amino groups and could be attributed to sugars, carboxylic acids, nucleic acids, or amino acids [ 26 ].…”
Section: Resultsmentioning
confidence: 85%
“…Our research group has developed several metal NP-based catalysts and their graphene nanocomposites and investigated their catalytic properties toward the oxidation of alcohols. ,, In our previously reported investigation, we reported that Ag 2 O NPs are highly effective dopants for MnO 2 , and the catalyst (1% Ag 2 O)–MnO 2 calcined at 400 °C afforded outstanding effectiveness for aerobic oxidation of a wide array of alcohols with the eco-friendly oxidant O 2 , which was later studied by doping the same with GRO and HRG, and their catalytic aptitude was also explored , Herein, we prepared novel Ag 2 O–MnO 2 /(X %)­N-DG nanocomposites via a facile and eco-friendly two-steps method with the coprecipitation procedure followed by the mechanochemical ball-milling procedure, as described in Scheme , and explored their efficacy with selective aerial oxidation of BlOH as a substrate model. The mechanochemical ball milling technique assists in the inhibition of agglomeration.…”
Section: Introductionmentioning
confidence: 99%